TINGKAT EFEKTIVITAS SOSIALISASI APLIKASI PEDULILINDUNGI TERHADAP SIKAP DAN OPINI MASYARAKAT - Riyansyah Saputra (2023)
This research aims to discuss the effectiveness level of PeduliLindungi App socialization on public's attitudes and opinions using Attribution Theory. This theory explains how a person concludes the cause of behavior by themselves or others. The method used is quantitative-descriptive research with the use of primary and secondary data sources. The sampling technique is done through Simple Random Sampling. Data was collected through a survey conducted on respondents who have used the PeduliLindungi Application. The survey includes questions related to the level of knowledge, understanding, usage, and perception of the community towards the PeduliLindungi Application. The final results of this research show that the level of effectiveness of the socialization of the PeduliLindungi Application is considered very high. The effectiveness level of PeduliLindungi App socialization on public's attitudes and opinions has an average of 90.76% based on the survey results from all respondents. The effectiveness level of PeduliLindungi App socialization on public's attitudes and opinions has an average of 91.49% based on the survey results from all respondents. These results provide a positive indication of The effectiveness level of PeduliLindungi App socialization, which is expected to bring significant benefits in the efforts to prevent and control the COVID-19 pandemic in Indonesia.